SdrLift: A Domain-Specific Intermediate Hardware Synthesis Framework for Prototyping Software-Defined Radios - Tsoeunyane, Lekhobola Joachim (Department of Electrical Engineering, 2021)
Modern design of Software-Defined Radio (SDR) applications is based on Field Programmable Gate Arrays (FPGA) due to their ability to be configured into solution architectures that are well suited to domain-specific problems while achieving the best trade-off between performance, power, area, and flexibility. FPGAs are well known for rich computational resources, which traditionally include logic, register, and routing resources. The increased technological advances have seen FPGAs incorporating more complex components that comprise sophisticated memory blocks, Digital Signal Processing (DSP) blocks, and high-speed interfacing to Gigabit Ethernet (GbE) and Peripheral Component Interconnect Express (PCIe) bus. Gateware for programming FPGAs is described at a lowlevel of design abstraction using Register Transfer Language (RTL), typically using either VHSIC-HDL (VHDL) or Verilog code. In practice, the low-level description languages have a very steep learning curve, provide low productivity for hardware designers and lack readily available open-source library support for fundamental designs, and consequently limit the design to only hardware experts. These limitations have led to the adoption of High-Level Synthesis (HLS) tools that raise design abstraction using syntax, semantics, and software development notations that are well-known to most software developers. However, while HLS has made programming of FPGAs more accessible and can increase the productivity of design, they are still not widely adopted in the design community due to the low-level skills that are still required to produce efficient designs. Additionally, the resultant RTL code from HLS tools is often difficult to decipher, modify and optimize due to the functionality and micro-architecture that are coupled together in a single High-Level Language (HLL). In order to alleviate these problems, Domain-Specific Languages (DSL) have been introduced to capture algorithms at a high level of abstraction with more expressive power and providing domain-specific optimizations that factor in new transformations and the trade-off between resource utilization and system performance. The problem of existing DSLs is that they are designed around imperative languages with an instruction sequence that does not match the hardware structure and intrinsics, leading to hardware designs with system properties that are unconformable to the high-level specifications and constraints. The aim of this thesis is, therefore, to design and implement an intermediatelevel framework namely SdrLift for use in high-level rapid prototyping of SDR applications that are based on an FPGA. The SdrLift input is a HLL developed using functional language constructs and design patterns that specify the structural behavior of the application design. The functionality of the SdrLift language is two-fold, first, it can be used directly by a designer to develop the SDR applications, secondly, it can be used as the Intermediate Representation (IR) step that is generated by a higher-level language or a DSL. The SdrLift compiler uses the dataflow graph as an IR to structurally represent the accelerator micro-architecture in which the components correspond to the fine-level and coarse-level Hardware blocks (HW Block) which are either auto-synthesized or integrated from existing reusable Intellectual Property (IP) core libraries. Another IR is in the form of a dataflow model and it is used for composition and global interconnection of the HW Blocks while making efficient interfacing decisions in an attempt to satisfy speed and resource usage objectives. Moreover, the dataflow model provides rules and properties that will be used to provide a theoretical framework that formally analyzes the characteristics of SDR applications (i.e. the throughput, sample rate, latency, and buffer size among other factors). Using both the directed graph flow (DFG) and the dataflow model in the SdrLift compiler provides two benefits: an abstraction of the microarchitecture from the high-level algorithm specifications and also decoupling of the microarchitecture from the low-level RTL implementation. Following the IR creation and model analyses is the VHDL code generation which employs the low-level optimizations that ensure optimal hardware design results. The code generation process per forms analysis to ensure the resultant hardware system conforms to the high-level design specifications and constraints. SdrLift is evaluated by developing representative SDR case studies, in which the VHDL code for eight different SDR applications is generated. The experimental results show that SdrLift achieves the desired performance and flexibility, while also conserving the hardware resources utilized.